Audit committees and accuracy of management earnings forecasts of Malaysian IPOs - Ammer, Mohammed Abdullah Ezzi (2015)
This study aims to make a meaningful contribution to the IPO literature by examining the impact of audit committee characteristics on the accuracy of earnings forecasts in 190 Malaysian IPO prospectuses during the period of 2002-2012. This study also adds to the body of knowledge by investigating the accuracy of IPO earnings forecasts during the former mandatory earnings forecasts (January 2002 to January 2008) and the current voluntary earnings forecasts (February 2008 to February 2012). Furthermore, it explores the provided explanations in the first published annual reports after IPO, which explain the reasons behind the errors of earnings forecasts. Two proxies were used for accuracy; absolute forecast error and squared forecast error. The models were developed using the frameworks of the agency theory, the signaling theory, and the resource-dependence theory to examine the association of eight characteristics of the audit committee (size, independence, financial expertise, gender diversity, ethnicity, stock ownership, educational background, and experience) with the accuracy of IPO earnings forecasts. The findings indicate that the earnings forecasts of Malaysian IPO are pessimistic and the percentage of accuracy is unsatisfactory. Further, the results show that Malaysian IPO earnings forecasts have been more pessimistic and less accurate under the voluntary regulation regime than the mandatory regime. The findings of multiple regressions of the audit committee and absolute forecast error show significant relationships with positive impacts among size, experience and accuracy of earnings forecasts. In terms of the findings of multiple regressions of the audit committee and the squared forecast error, the results show significant relationships with positive impacts between size and earnings forecasts accuracy. Finally, the results indicate that the number of provided explanations was greater when the management were more optimistic and the forecasts errors were large. The results of this study can be of interest to investors, policymakers, investment analysts and other market participants